The role of TNF-α as a marker of apoptotic response in Iraqi patients infected with Helicobacter pylori - Hussein , Shahad Ahmed; Al-Hindi , Zeana S. (Hammurabi Journal of Medical Sciences, 2024)
Background: Tumor necrosis factor is one of the host genetic variables that influence susceptibility to illnesses associated with Helicobacter pylori infections. Objectives: Determination of apoptosis response in H. Pylori patients by an immunological marker TNF-α level. Materials and Methods: The study involved (110) of infected H. pylori and healthy from Nov, 2023 to Jan, 2024 from the Digestive center in Merjan Medical City. The levels of TNF-α were measured using the enzyme-linked immunosorbent assay. Results: The results showed the highest rate of infection in males (56.4%) compared to females (43.6 %). The incidence of Helicobacter pylori were distributed in different blood groups [B, O, A, and AB]. [O] Group had the highest incidence of rate (34.5%). According to the data, the percentage was lowest in rural areas (40.9%) and highest in urban (59. 1%). The present investigation showed, only female granulocytes demonstrated significant (p≤0.05) immune cell counts about (4.8086 ± 1.59457 pm/ml), whereas male total immune cell counts had significant as (7.9621 ± 2.60552pm/ml). Immunological tests for patients showed increased TNF-α concentration at varied age groups in comparison to the control group and the age group with the largest concentration of them (41.28529 ± 6.169497pg/ml). One-way ANOVA shows a non-significant difference under (p ≤ 0.05). Conclusion: The present investigation pointed to the correlation subject between TNF-α and WBC, result found there is an inverse correlation between them in patients with the present relationship in control, which ensures an important of immune regulation. Those achieve the aim of our study as can help comprehend the process by which Helicobacter pylori cause cell death and how it relates to the pathophysiology of stomach illness.